2019
DOI: 10.1101/gad.320127.118
|View full text |Cite
|
Sign up to set email alerts
|

TGIF transcription factors repress acetyl CoA metabolic gene expression and promote intestinal tumor growth

Abstract: Tgif1 (thymine-guanine-interacting factor 1) and Tgif2 repress gene expression by binding directly to DNA or interacting with transforming growth factor (TGF) β-responsive SMADs. Tgifs are essential for embryogenesis and may function in tumor progression. By analyzing both gain and loss of Tgif function in a well-established mouse model of intestinal cancer, we show that Tgifs promote adenoma growth in the context of mutant Apc (adenomatous polyposis coli). Despite the tumor-suppressive role of TGFβ signaling,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…In harmony with an oncogenic role of TGIF in breast cancer, silencing of TGIF was found to suppress the migration, invasion and metastasis of the human breast cancer cells in both in vitro and in vivo experiments ( Wang et al, 2018c ). TGIF1 has also been found to be significantly upregulated in some colorectal cancers and to promote adenoma growth in the context of mutant Apc ( Shah et al, 2019 ). Overexpression of TGIF1 markedly promoted the proliferation of colorectal cancer cells through the activation of Wnt/β-catenin signaling ( Wang et al, 2017c ).…”
Section: Examples Of Genes With Strong Signatures Of Positive And/or mentioning
confidence: 99%
See 1 more Smart Citation
“…In harmony with an oncogenic role of TGIF in breast cancer, silencing of TGIF was found to suppress the migration, invasion and metastasis of the human breast cancer cells in both in vitro and in vivo experiments ( Wang et al, 2018c ). TGIF1 has also been found to be significantly upregulated in some colorectal cancers and to promote adenoma growth in the context of mutant Apc ( Shah et al, 2019 ). Overexpression of TGIF1 markedly promoted the proliferation of colorectal cancer cells through the activation of Wnt/β-catenin signaling ( Wang et al, 2017c ).…”
Section: Examples Of Genes With Strong Signatures Of Positive And/or mentioning
confidence: 99%
“…TGIF1 has also been found to be significantly upregulated in some colorectal cancers and to promote adenoma growth in the context of mutant Apc ( Shah et al, 2019 ). Overexpression of TGIF1 markedly promoted the proliferation of colorectal cancer cells through the activation of Wnt/β-catenin signaling ( Wang et al, 2017c ).…”
Section: Examples Of Genes With Strong Signatures Of Positive And/or mentioning
confidence: 99%
“…Moreover, miR-296 is also indicative of metastasis and epithelial-mesenchymal transition of CRC [ 13 ]. Thymine-guanine-interacting factors (TGIFs) are up-regulated in mutant colon tumors which assist to reprogram the expression of metabolic genes [ 14 ]. TGIF1 is a transcriptional co-repressor which exerts as a tumor promoter of CRC exacerbation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that TGIF1 plays a critical role in tumor initiation and progression, and its overexpression is associated with a poor prognosis of patients with colorectal ( 10 , 11 ), lung ( 12 ), gastric ( 22 ) and breast ( 13 , 23 ) cancer. The study by Wang et al demonstrated that TGIF1 was upregulated in colorectal cancer and functioned as an oncogene, promoting cancer cell proliferation and migration ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely accepted that TGFB induced factor homeobox 1 (TGIF1), a member of the TGIF family, functions as a transcriptional repressor of TGF-β signaling and retinoid X receptor (RXR) signaling ( 7 , 8 ). Recent studies have demonstrated that TGIF is also involved in Wnt/β-catenin signaling ( 9 , 10 ) and regulates basic energy metabolism in cells ( 11 ). Consistent with the critical roles of TGIF1 in the regulation of important signaling pathways, TGIF1 has also been shown to be involved in tumorigenesis and tumor development, such as in lung ( 12 ), breast ( 13 ) and colorectal ( 14 ) cancer.…”
Section: Introductionmentioning
confidence: 99%